2019
DOI: 10.1002/mp.13350
|View full text |Cite
|
Sign up to set email alerts
|

Multislice motion modeling forMRI‐guided radiotherapy gating

Abstract: Purpose On‐board magnetic resonance imaging (MRI) greatly enhances real‐time target tracking capability during radiotherapy treatments. However, multislice and volumetric MRI techniques are frame rate limited and introduce unacceptable latency between the target moving out of position and the beam being turned off. We present a technique to estimate continuous volumetric tissue motion using motion models built from a repeated acquisition of a stack of MR slices. Applications including multislice target visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The average registration consistency was 0.77 mm. These values are similar to those reported in our previous publications …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The average registration consistency was 0.77 mm. These values are similar to those reported in our previous publications …”
Section: Resultssupporting
confidence: 93%
“…Notably, the other authors estimated motion across multiple slices whereas the present study predicted motion in a single imaging plane . Our technique is generalizable and could be combined with a LLE‐based multi‐slice motion modeling method to perform multi‐slice motion prediction …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As out-of-plane motion can occur when a single 2D slice is used, the acquisition of several parallel slices [12,49] or the interleaved [50][51][52][53] or simultaneous [54,55] acquisition of orthogonal slices has been investigated. Acquiring imaging data from different orientations could indeed enable the real-time reconstruction of the anatomy in 3D [53].…”
Section: Imaging For Motion Monitoringmentioning
confidence: 99%
“…Note that this process is currently 2D, due to a lack of commercially available real-time 3D imaging sequences. Recent studies however showed promising approaches towards realtime 3D MR image acquisition (53)(54)(55)(56) and reconstruction (57).…”
Section: Real-time Mrimentioning
confidence: 99%